Variability in coriander (Coriandrum sativum L.) for yield and yield components - Singh, S S Rajput, Dhirendra (Journal of Spices and Aromatic Crops, 2003)
Studies on variability in twenty genotypes of Coriandrum sativum L. indicated higher estimates of genotypic coefficient of variation, phenotypic coefficient of variation, heritability and genetic advance for seed yield, ulnbels plantl, seeds umbeI-l and plant height, suggesting probable role of additive gene effects on character expression. Superior genotypes for different, traits identified in the study could be exploited for inter varietal hybridization (reciprocal recurrent selection method) for evolving a high yielding variety with other desirable traits.